Ixekizumab Real-World Effectiveness at 24 Weeks in Patients with Psoriasis: Data from the United States Taltz Customer Support Program - Alice B. Gottlieb; Russel Burge; William N. Malatestinic; Baojin Zhu; Yunyang Zhao; Julie McCormack; Miriam Kimel; Joseph F. Merola (Adis, Springer Healthcare, 2023)
Abstract Introduction Ixekizumab, a highly selective interleukin-17A monoclonal antibody, was approved for the treatment of moderate-to-severe psoriasis (PsO) in 2016. Limited real-world data are available on its effectiveness from a patient's perspective shortly (2 to 4 weeks) after initiation and upon continuation for 24 weeks. Objective To describe patient-reported clinical and quality-of-life outcomes after initiating ixekizumab using data collected from the United States Taltz® Customer Support Program. Methods This was a 24-week prospective, observational study of commercially insured diagnosis-confirmed adults with PsO. Surveys were completed at weeks 0 (baseline), 2, 4, 8, 12, and 24 and included the Patient Report of Extent of Psoriasis Involvement questionnaire to assess the extent of body surface area (BSA) affected by PsO, itch and pain numeric rating scales, Patient Global Assessment of Disease Severity (PatGA), and Dermatology Life Quality Index (DLQI). Results 523 patients were included in the analysis. Proportions of patients with ≤ 2% BSA involvement were 34.5%, 40.1%, 50.9%, and 79.9% at weeks 0, 2, 4, and 24, respectively; 54.8% and 75.1% achieved National Psoriasis Foundation preferred (BSA ≤ 1%) and acceptable (BSA ≤ 3% or ≥ 75% improvement) responses at week 12, respectively. Improvements of ≥ 4 points in itch and pain were seen by week 2 in 21.1% and 28.0% of patients, respectively, which increased to 63.1% and 64.8% at week 24. Proportions of patients with PatGA scores of 0 (clear) or 1 were 13.4%, 24.1%, 34.0%, and 69.6% at weeks 0, 2, 4, and 24, respectively; and proportions with DLQI total scores of 0 or 1 [no or minimal impact] were 8.4%, 17.6%, 27.3%, and 53.8% at weeks 0, 2, 4, and 24, respectively. Conclusion Patient-reported improvements in BSA, itch, skin pain, dermatology-specific quality of life, and overall PsO severity were seen as early as 2 weeks after initiation and continued through week 24.